Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales